High-Performance Wearable Bi2Te3-Based Thermoelectric Generator - Yubing Xing; Kechen Tang; Jiang Wang; Kai Hu; Yani Xiao; Jianan Lyu; Junhao Li; Yutian Liu; Peng Zhou; Yonggao Yan; Dongwang Yang (Applied Sciences, 2023)
Wearable thermoelectric generators (w-TEGs) convert thermal energy into electrical energy to realize self-powering of intelligent electronic devices, thus reducing the burden of battery replacement and charging, and improving the usage time and efficiency of electronic devices. Through finite element simulation, this study successfully designed high-performance thermoelectric generator and made it into wearable thermoelectric module by adopting “rigid device—flexible connection” method. It was found that higher convective heat transfer coefficient (h) on cold-end leads to larger effective temperature difference (ΔTeff) and better power generation performance of device in typical wearable scenario. Meanwhile, at same h on the cold-end, longer TE leg length leads to larger ΔTeff established at both ends of device, larger device output power (Pout) and open-circuit voltage (Uoc). However, when the h increases to a certain level, optimization effect of increasing TE leg length on device power generation performance will gradually diminish. For devices with fixed temperature difference between two ends, longer TE leg length leads to higher resistance of TEGs, resulting in lower device Pout but slight increase in Uoc. Finally, sixteen 16 × 4 × 2 mm2 TEGs (L = 1.38 mm, W = 0.6 mm) and two modules were fabricated and tested. At hot end temperature Th = 33 °C and cold end temperature Tc = 30 °C, the actual maximum Pout of the TEG was about 0.2 mW, and the actual maximum Pout of the TEG module was about 1.602 mW, which is highly consistent with the simulated value. This work brings great convenience to research and development of wearable thermoelectric modules and provides new, environmentally friendly and efficient power solution for wearable devices.